Determination of Arsenic in Tuul River and in Drinking Water, using HG-AAS with Electrically Heated Atomizer - Tsetsegmaa, T; Darjaa, Ts; Dorj, D (Proceedings of the Mongolian Academy of Sciences, 2011)
The electrothermal atomizer was installed in a Varian AA240FS AAS. This equipment was tested for determination of arsenic by hydride generation – atomic absorption method in water samples in the low μg/l range. Pre-reduction capability of KI investigated systematically and obtained as 2.5 %. Analytical parameters, that influencing for hydride formation NaBH4 and HCl concentrations are optimized and employed as 0.5 % and 8 mol/l accordingly. The detection limit for determination of arsenic by optimized HG-AAS with electrically heated atomizer was 0.3 μg/l. The accuracy is confirmed by optimized HG-AAS method with flame atomizer and by ICP-MS. Water samples were taken from the different places of Tuul river and from groundwater in the same area. It was found that the arsenic concentration in the river was low, around 3 ppb. The concentration of arsenic in groundwater was around the detection limit of method and no detectable amount of arsenic was found in the other. Concentration of arsenic in the Tuul river in these districts does not seem to be so high that it could affect the people living there. DOI: http://dx.doi.org/10.5564/pmas.v0i4.50 Proceedings of the Mongolian Academy of Sciences 2009 No.4 pp.78-85